THE DYNAMICS OF FAMILY-OWNED SME SUSTAINABILITY IN RURAL AREAS [DINAMIKA KEBERLANJUTAN UKM KELUARGA DI PEDESAAN] - Muhammad Setiawan Kusmulyono (Universitas Pelita Harapan, 2023)
SMEs in rural areas have characteristics that are closely related to the character of a family business. This can be seen in the management of the SME business which is fully controlled by the family. This situation shows that SMEs in rural areas are more dominated by family-owned SMEs. As a family-owned SME, this village entrepreneur has a big challenge to be able to regenerate the business for the next generation. This study seeks to identify the things that affect the dynamics in realizing the sustainability of family-owned SMEs in the village. This study uses a qualitative approach by conducting interviews through purposive sampling to culinary informants who run their businesses in rural areas and have the next generation. The results of the study show that in addition to all SMEs in the village being dominated by family businesses, these SMEs have hopes that their families will continue their business, but on the other hand it was also found that there are SMEs who do not care who will continue their business. This study produces interesting findings that can be developed to help improve the sustainability of SME development in Indonesia. Abstrak dalam Bahasa Indonesia. UKM di pedesaan memiliki karakteristik yang erat kaitannya dengan karakter usaha keluarga. Hal ini terlihat dari pengelolaan usaha UKM yang sepenuhnya dikendalikan oleh keluarga. Keadaan ini menunjukkan bahwa UKM di pedesaan lebih didominasi oleh UKM milik keluarga. Sebagai UKM milik keluarga, pengusaha desa ini memiliki tantangan besar untuk bisa meregenerasi bisnisnya untuk generasi selanjutnya. Kajian ini berupaya mengidentifikasi hal-hal yang mempengaruhi dinamika dalam mewujudkan keberlanjutan UKM milik keluarga di desa. Penelitian ini menggunakan pendekatan kualitatif dengan melakukan wawancara melalui purposive sampling kepada informan kuliner yang menjalankan usahanya di pedesaan dan memiliki generasi penerus. Hasil kajian menunjukkan bahwa selain seluruh UKM yang ada di desa didominasi oleh usaha keluarga, UKM ini memiliki harapan agar keluarganya tetap melanjutkan usahanya, namun disisi lain juga ditemukan adanya UKM yang tidak peduli yang akan melanjutkan usahanya. Kajian ini menghasilkan temuan menarik yang dapat dikembangkan untuk membantu meningkatkan keberlanjutan pengembangan UKM di Indonesia.